Ökumenische Rundschau: A Protestant Ecumenical Journal and Its Role in the Ecumenical Movement. Issue 2 (25th June 2022) - Heller, Dagmar
Abstract: This article reviews the history of Ökumenische Rundschau, an ecumenical journal founded in Germany in 1952. It examines the journal's relationship to the church landscape in Germany as well as its links to the worldwide ecumenical movement and the World Council of Churches. The article reviews the institutional development of the journal and the themes and content of the journal over the years.